Unbalanced Economic Growth and Dynamic Trade Specialization - Tri Widodo; Samsubar Saleh (Journal of World Trade Studies, 2010)
This paper examines the impact of unbalanced economic growth upon countries’ dynamic trade specialization. Firstly, we identify theoretically the impact. Secondly, we construct an econometric model to investigate the impact. We employ revealed symmetric comparative advantage (RSCA) index as an indicator of trade specialization and coefficient of variation (CV) of sectoral output growth as an indicator of unbalanced economic growth. Thirdly, we apply empirically the model in the cases of Korea, Singapore, Indonesia and Malaysia. We conclude that domestic unbalanced economic growth has a positive and statistically significant impact on dynamic trade specialization in the cases of Indonesia and Malaysia, but not in the cases of Korea and Singapore. However, the world unbalanced economic growth has a statistically insignificant impact on the all selected countries’ dynamic trade specialization.